Performance optimization of asphalt pavements using binder film thickness as a criterion in innovative mix design compared to Marshall and Superpave methods - Khan, Muhammad Adeel; Khan, Muhammad Salman; Nasir, Bilal; Khan, Asad; Sabri, Mohanad Muayad Sabri; Ahmad, Mahmood; Qamar, Wajeeha; Gonzalez-Lezcano, Roberto Alonso (Frontiers in Materials, 2025)
The performance of asphalt pavements is significantly influenced by the mix design and the binder film thickness (BFT) around aggregates. Adjusting the proportions of binders and aggregates modifies the properties of asphalt mixtures, with different mix designs substantially impacting these properties. This study evaluates the influence of two traditional mix designs (i.e., Marshall and Superpave Gyratory Compacted) and one innovative mix design (the one using BFT as a criterion) on asphalt pavement performance Two methods, which are modifications of the Hveem Surface Area Factor method, were used to calculate the optimum BFT. The mix with 3.5% asphalt content (AC) was selected for the innovative mix design as it showed the optimal BFT. For the Marshall and Superpave mix designs, the optimum binder content was determined using the respective Marshall and Superpave Gyratory Compacted methods, yielding values of 4.3% and 4.4%, respectively. Samples were prepared from each type of mix design and then tested using a Universal Testing Machine (UTM) and a Double Wheel Tracker (DWT). Performance tests showed that the innovative mix design samples had superior rutting resistance under DWT, the Marshall samples had the highest Resilient Modulus (Mr) and moisture resistance, and the Superpave samples exhibited the best fatigue resistance, enduring the most cycles until failure in the Indirect Tensile Fatigue Test (ITFT). These findings underscore the importance of considering BFT as a critical mix design criterion, demonstrating its significant potential to enhance the overall performance and durability of asphalt pavements.